Robotic Seals as Therapeutic Tools in an Aged Care Facility: A Qualitative Study - Melanie Birks; Marie Bodak; Joanna Barlas; June Harwood; Mary Pether (Journal of Aging Research)
Robots, including robotic seals, have been used as an alternative to therapies such as animal assisted therapy in the promotion of health and social wellbeing of older people in aged care facilities. There is limited research available that evaluates the effectiveness of robot therapies in these settings. The aim of this study was to identify, explore, and describe the impact of the use of Paro robotic seals in an aged care facility in a regional Australian city. A qualitative, descriptive, exploratory design was employed. Data were gathered through interviews with the three recreational therapists employed at the facility who were also asked to maintain logs of their interactions with the Paro and residents. Data were transcribed and thematically analysed. Three major themes were identified from the analyses of these data: “a therapeutic tool that’s not for everybody,” “every interaction is powerful,” and “keeping the momentum.” Findings support the use of Paro as a therapeutic tool, revealing improvement in emotional state, reduction of challenging behaviours, and improvement in social interactions of residents. The potential benefits justify the investment in Paro, with clear evidence that these tools can have a positive impact that warrants further exploration.